PENGARUH MODEL PROJECT BASED LEARNING PADA MATA KULIAH PENDIDIKAN KEWARGANEGARAAN TERHADAP KARAKTER INTEGRASI NASIONAL MAHASISWA TEKNIK INFORMATIKA - Ita Aristia Sa'ida (EDU RESEARCH, 2022)
To achieve the learning objectives of civic education, strategies and models are needed in learning that can increase student participation and creativity and be able to instil character values in students and national integration of informatics engineering students. To instil character values in students and national integration of informatics engineering students, researchers chose a Project-Based Learning model based on projects / activities as a medium. Through this project-based learning, lecturers are required to be able to shape and build the character of students who love the country and are able to carry out foreign activities. For this reason, the author is interested in conducting research with the theme "The Effect of the Project Based Learning Model in the Civic Education course on the national integration character of Informatics Engineering students". The purpose of this study is to determine whether or not there is an effect of the Project Based Learning Model in the Civics Education course on the national integration character of Informatics Engineering students. Data analysis used in this study includes normality, homogeneity and hypothesis testing. Based on the results of research and discussion, it is obtained that the data is normally distributed and homogeneous, then proceed to hypothesis testing. Based on the hypothesis test that has been carried out so that the sig value is obtained. (2-tailed) = 0.000 < ∝ = 0.05 means H0 is rejected and H1 is accepted so it can be concluded that there is an effect of the Project Based Learning Model in the Civic Education course on the national integration character of Informatics Engineering students.